2009
DOI: 10.1007/s10552-009-9449-1
|View full text |Cite
|
Sign up to set email alerts
|

Depression and cancer risk: 24 years of follow-up of the Baltimore Epidemiologic Catchment Area sample

Abstract: Objective The objective was to characterize the relationship between depression and incident cancer. Few studies have employed population-based prospective data on subtypes of cancer to address the question. Method A population-based sample of 3,177 cancer-free adults from the Baltimore Epidemiologic Catchment Area Study who have been followed for 24 years. Cox proportional hazards models were used to estimate relative hazards for both overall and subtype-specific cancers among those with a history of depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 35 publications
9
119
3
4
Order By: Relevance
“…It may be comparable with The Danish cohort study, which detected a marginally significantly lower risk for reactive depression, and the possibility of decreased motivation for surveillance among patients with depressed mood should be considered (7). Positive relationship between depression and breast cancer may exist (6,8), but most researches did not show this association (3). Although showing the tendency of positive relationship, our data did not support any significant finding for breast caner either.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It may be comparable with The Danish cohort study, which detected a marginally significantly lower risk for reactive depression, and the possibility of decreased motivation for surveillance among patients with depressed mood should be considered (7). Positive relationship between depression and breast cancer may exist (6,8), but most researches did not show this association (3). Although showing the tendency of positive relationship, our data did not support any significant finding for breast caner either.…”
Section: Discussionsupporting
confidence: 49%
“…One large study with long follow-up time conducted in Baltimore area showed that major depression was associated with a higher hazard for overall cancer, as well as for breast cancer and prostate cancer, and the authors suggested the association between depression and hormonally medicated cancers (6). Another nationwide cohort study from Denmark found that the standardized incidence ratio was 1.05 (95% CI ¼ 1.03-1.07) and concluded that most of the excess risk could be attributed to an increased risk of tobacco-related cancers (7).…”
Section: Discussionmentioning
confidence: 99%
“…Although EGFR mutations may reduce the risk for depression, chronic depression may possibly be associated with a higher risk for developing wild-type EGFR tumors. Epidemiological data have yielded mixed results for depression being associated with a higher risk for lung cancer, but these data did not subdivide the lung cancers by EGFR genotype [32,33]. Nonetheless, results from large clinical trials of advanced NSCLC patients have shown that EGFR tyrosine kinase inhibitors have beneficial effects on mood.…”
Section: Discussionmentioning
confidence: 99%
“…Women with metastatic breast cancer have been studied by Ambercrombie et al and also revealed flatter cortisol slopes compared to a healthy control population. It has been assumed that such abnormalities could be due to many causes such as a Hypothalamic -Pituitary-Adrenal (HPA) feedback system malfunction, hypersensitivity towards stress, inability to inactivate cortisol and even sleep irregularities 20,21) . Nilsen et al, concluded after a 19 year follow up survey of 18,932 women that those working in highly fast paced jobs are more prone to breast cancer than women working at a slower pace.…”
Section: Cortisol and Cancer: Clinical Evidencementioning
confidence: 99%